The Impact of Big Snake and Ladders Instructional Media on English Learning Outcomes of Elementary School Students - Muhammad Sofyan Sauri; Mursalim; Matkur (Program Studi PGMI, 2026)
This study aims to examine the effect of Big Snake and Ladders instructional media on elementary school students’ learning outcomes. The research employed a quantitative approach using a quasi-experimental nonequivalent control group design. The participants were fifth-grade students of SDN Glundengan 02 Wuluhan Jember, with class VA as the experimental group (n = 24) and class VB as the control group (n = 23). Data were collected through pre-test and post-test learning outcome assessments. Normality test results indicated that all data were normally distributed (Sig. > 0.05), and homogeneity tests confirmed equal variances between groups (pre-test Sig. = 0.209; post-test Sig. = 0.772). Descriptive analysis revealed that the experimental group achieved a higher post-test mean score (M = 75.63, SD = 12.71) compared to the control group (M = 70.43, SD = 12.78), with a mean difference of 5.19 points. The independent sample t-test showed a statistically significant difference (t = 3.395, Sig. (2-tailed) = 0.000 < 0.05). These findings indicate that Big Snake and Ladders instructional media significantly improve elementary students’ learning outcomes and can be effectively integrated into classroom instruction.